A sulfated sodium alginate hydrogel and its preparation method and application

By designing a sulfated sodium alginate hydrogel with pH-responsive drug release function, the problem of difficulty in wound healing in diabetic patients is solved, the effect of promoting neovascularization and inhibiting inflammation is achieved, and the healing rate and quality of diabetic wounds is significantly improved.

CN114891240BActive Publication Date: 2025-03-25OCEAN UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210395153.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-15
Publication Date
2025-03-25
Estimated Expiration
2042-04-15

AI Technical Summary

Technical Problem

The wounds of diabetic patients are difficult to heal due to chronic inflammation and angiogenesis disorders in the hyperglycemia environment, and the weak acidity of the wound environment promotes bacterial reproduction and increases the risk of infection.

Method used

A sulfated sodium alginate hydrogel with pH-responsive drug release function was designed, prepared by chemical crosslinking methods, with crosslinking agents introduced to regulate pore size and rheological properties, used as wound dressings to promote neovascularization and inhibit inflammation.

Benefits of technology

The hydrogel has a large surface area and pore size structure, realizes the sustained release of ferroamine methanesulfonate, promotes wound neovascularization, effectively isolates wound wounds, has good breathability, and can absorb inflammatory factors at the wound site, promotes healing, and relieves chronic inflammation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114891240B_ABST
    Figure CN114891240B_ABST
Patent Text Reader

Abstract

The present invention provides a sulfated sodium alginate hydrogel and a preparation method and application thereof. The sulfated sodium alginate hydrogel is prepared from sulfated sodium alginate, adipic acid dihydrazide, polyethylene glycol and deferoxamine mesylate. The preparation method of the sulfated sodium alginate hydrogel of the present invention is simple and efficient and has injectability, self-healing properties and pH responsiveness, and can promote fibroblast migration, promote angiogenesis, inhibit inflammation, and promote the healing of chronic wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical materials, and in particular to a sulfated sodium alginate hydrogel and a preparation method and application thereof. Background Art

[0002] Diabetes is a disease caused by insufficient insulin secretion or insulin resistance. Most diabetic patients suffer from various complications, including cardiovascular disease, nerve damage, kidney damage, etc., especially delayed wound healing. Once the wound of a diabetic patient is formed, it is difficult to heal due to chronic inflammation and angiogenesis disorders caused by the hyperglycemic environment. Due to the hyperglycemic wound environment, diabetic wounds produce excessive lactic acid and acetic acid, resulting in a weakly acidic environment in the wound and a large number of bacteria. Therefore, by utilizing the weakly acidic environment of diabetic wounds, a smart hydrogel with pH-responsive drug release function is designed, which can reduce chronic inflammation at the diabetic wound site and promote angiogenesis, which will be beneficial to promote the healing of chronic diabetic wounds.

[0003] Hydrogels are new functional polymer materials with three-dimensional network structures that can swell completely in water without dissolving. Due to their biocompatibility and biodegradability, they have been widely used in drug delivery, cell therapy and wound healing. In particular, hydrogels based on natural polysaccharides such as heparin, chitosan and hyaluronic acid are used as transport carriers for drugs, proteins or cells, and as scaffold materials for tissue regeneration. Summary of the invention

[0004] The invention provides a sulfated sodium alginate hydrogel and a preparation method and application thereof. The hydrogel can be used for chronic wound repair, especially chronic inflammatory wound repair caused by diabetes.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a sulfated sodium alginate hydrogel, which specifically comprises the following steps:

[0007] (1) dissolving sodium alginate in a chlorosulfonic acid formamide mixed solution to react, obtaining sulfated sodium alginate, re-dissolving by alcohol precipitation, dialysis and freeze-drying to obtain sulfated sodium alginate;

[0008] (2) dissolving sulfated sodium alginate and sodium periodate in ultrapure water, adding ethylene glycol to quench after the reaction in the dark, and freeze-drying to obtain oxidized sulfated sodium alginate;

[0009] (3) dissolving deferoxamine mesylate in a buffer solution containing polyethylene glycol to obtain a deferoxamine mesylate solution;

[0010] (4) dissolving oxidized sulfated sodium alginate in a deferoxamine methanesulfonate solution to obtain solution A; dissolving adipic acid dihydrazide in a deferoxamine methanesulfonate solution to obtain solution B;

[0011] (5) Mix solution A and solution B evenly to obtain sulfated sodium alginate hydrogel.

[0012] Furthermore, the mass volume ratio of the sodium alginate and chlorosulfonic acid formamide mixed solution in step (1) is 1:8-10, wherein the chlorosulfonic acid formamide mixed solution is prepared by mixing chlorosulfonic acid and anhydrous formamide in a volume ratio of 1:4-6.

[0013] Furthermore, in the step (1), the sodium alginate is dissolved in the chlorosulfonic acid formamide mixed solution at a reaction temperature of 60° C. to 70° C. and a reaction time of 2 h to 4 h.

[0014] Furthermore, in step (2), the molar ratio of sulfated sodium alginate to sodium periodate is 2:1 to 1:1.

[0015] Preferably, in step (2), the molar ratio of sulfated sodium alginate to sodium periodate is 1:0.6.

[0016] Furthermore, the final concentration of the deferoxamine mesylate solution in step (3) is 60 μg / mL-100 μg / mL.

[0017] Preferably, the final concentration of the deferoxamine mesylate solution in step (3) is 80 μg / mL.

[0018] Furthermore, in step (4), the final concentration of solution A is 50 mg / mL-80 mg / mL, and the final concentration of solution B is 5 mg / mL-20 mg / mL.

[0019] Preferably, in step (4), the final concentration of solution A is 60 mg / mL, and the final concentration of solution B is 15 mg / mL.

[0020] Furthermore, in step (5), solution A and solution B are mixed in a volume ratio of 3 to 5:1 and vortexed at room temperature for 10 to 30 minutes.

[0021] Furthermore, the preparation method specifically comprises the following steps:

[0022] (1) dissolving sodium alginate in a chlorosulfonic acid formamide mixed solution to react, obtaining sulfated sodium alginate, precipitating with alcohol, and then re-dissolving with water, placing the alginate in a 3500Da dialysis bag, dialyzing until the conductivity is less than 3 μs / cm, and then freeze-drying to obtain sulfated sodium alginate S-SA;

[0023] (2) 0.5 g S-SA and 0.321 g NaIO4 were dissolved in 100 mL ultrapure water, and the mixture was reacted in the dark for 4 h. Then, ethylene glycol in an amount equal to the mole of NaIO4 was added to quench the mixture, and the mixture was freeze-dried to obtain oxidized sulfated sodium alginate (S-OSA);

[0024] (3) Weigh 4 mg of deferoxamine mesylate (DFO) and dissolve it in 50 mL of 5 mg / mL PEG solution. Vortex until completely dissolved to prepare an 80 μg / mL DFO solution.

[0025] (4) Dissolve 375 mg of S-OSA in DFO solution to obtain solution A; dissolve 75 mg of adipic acid dihydrazide ADH in 5 mL of DFO solution to obtain solution B;

[0026] (5) Take 0.8 mL of S-OSA solution, add 0.2 mL of ADH solution thereto, stir quickly and evenly on a vortex oscillator, transfer to a mold, and place at room temperature for a period of time to form a gel, thereby obtaining sulfated sodium alginate (S-OSA-DFO) hydrogel.

[0027] The invention also provides a sulfated sodium alginate hydrogel prepared by the preparation method. The sulfated sodium alginate hydrogel is cross-linked with sulfated oxidized sodium alginate, adipic acid dihydrazide, polyethylene glycol and deferoxamine mesylate.

[0028] The present invention also provides the use of the sulfated sodium alginate hydrogel in preparing external medicines or medical functional dressings for repairing chronic wounds.

[0029] Furthermore, the chronic wound is caused by trauma, diabetic complications, etc.

[0030] Furthermore, filling the sulfated sodium alginate hydrogel into the wound site of chronic trauma can promote angiogenesis and inhibit inflammation, thereby promoting wound healing.

[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0032] The sulfated sodium alginate hydrogel of the present invention is prepared by a chemical cross-linking method, and the preparation method is simple and efficient. In the preparation process, by introducing a cross-linking agent, the concentration of the cross-linking agent is adjusted, the pore size and rheological properties of the hydrogel are regulated, and the prepared hydrogel has a larger surface area and pore structure, and the sustained release of deferoxamine mesylate can be achieved, promoting the hyperplasia of new blood vessels at the wound site. In addition, when the hydrogel is used as a wound dressing, the wound surface can be effectively isolated, and the dense gel network aperture gives the hydrogel good air permeability.

[0033] In addition to having the functions of conventional wound dressings, this hydrogel can effectively absorb inflammatory factors at the wound site, promote the transition from the inflammatory phase to the proliferative phase during wound healing, and thereby alleviate the occurrence of chronic inflammation at the wound site. In addition, this hydrogel can promote the migration of fibroblasts and the expression of VEGF and CD31, etc., and can comprehensively promote chronic wound healing in the early and late stages of wound healing.

[0034] The sulfated sodium alginate hydrogel provided by the present invention has high safety, good biocompatibility, can effectively treat difficult-to-heal wounds caused by chronic inflammation, and has great application prospects in the treatment of diabetic wounds. The present invention is suitable for the treatment and care of diabetic chronic wounds, which are widely present in clinical practice, especially wounds caused by diabetic chronic inflammation. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the scanning electron microscopy spectrum of sulfated sodium alginate hydrogel.

[0036] FIG. 2 shows the self-healing results (A) and injectability results (B) of sulfated sodium alginate hydrogel.

[0037] Figure 3 is the cumulative drug release of sulfated sodium alginate hydrogel under different pH conditions.

[0038] Figure 4 These are the results of characterization of the physicochemical properties of sulfated sodium alginate hydrogel.

[0039] Figure 5 This is the hemolysis rate result of sulfated sodium alginate hydrogel.

[0040] Figure 6 These are the results of the sulfated sodium alginate hydrogel cell viability experiment.

[0041] Figure 7 The results of the sulfated sodium alginate hydrogel cell migration experiment.

[0042] Figure 8 This is the wound healing status of diabetic rats at different times.

[0043] FIG. 9 shows the histological experimental results of sulfated sodium alginate hydrogel, wherein A is the H&E staining result and B is the Masson staining result.

[0044] Fig.10 Figure 2 shows the changes in the levels of inflammatory factors in the wound site, where A is the immunohistochemical image of IL-6 on the 5th and 10th days; B is the immunohistochemical image of TNF-α on the 5th and 10th days; C is the immunohistochemical image of VEGF on the 10th and 14th days; and D is the immunohistochemical image of CD31 on the 10th and 14th days. DETAILED DESCRIPTION

[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the present invention equally.

[0046] Example 1: Preparation of sulfated sodium alginate hydrogel

[0047] (1) Weigh 5 g of sodium alginate (SA) and dissolve it in 43.5 mL of a chlorosulfonic acid-formamide mixed solution (wherein the volume of chlorosulfonic acid is 8 mL and the volume of anhydrous formamide is 35.5 mL). React in an oil bath at 64° C. for 3 h. After the sulfation of the sodium alginate is completed, cool to room temperature, add three times the volume of 85% ethanol to the cooled reaction solution for precipitation, centrifuge at 3000 rpm for 15 min, separate the supernatant and the precipitate, discard the supernatant, and then wash the remaining precipitate with an appropriate amount of 75% ethanol for more than three times, continue to centrifuge at 3000 rpm for 15 min, discard the supernatant, add water to dissolve, place in a 3500 Da dialysis bag, and dialyze with deionized water until the conductivity is less than 3 μs / cm. After the dialysis is completed, the dialyzate is concentrated and freeze-dried to obtain white powdery sulfated sodium alginate (S-SA).

[0048] (2) Weigh 5 g of sulfated sodium alginate and 4.28 g of sodium periodate (NaIO4), dissolve in 100 mL of ultrapure water, react at room temperature in the dark for 4 h, add 20 mL of ethylene glycol to quench and terminate the reaction. Then dialyze with ultrapure water to remove unreacted sodium periodate and ethylene glycol until the conductivity is less than 3 μs / cm. After the dialysis is completed, the dialysate is concentrated and freeze-dried to obtain white powdery oxidized sulfated sodium alginate (S-OSA).

[0049] The above reaction formula is as follows:

[0050]

[0051] (3) Weigh 4 mg of deferoxamine mesylate and dissolve it in 50 mL of polyethylene glycol (5 mg / mL) in PBS buffer solution (pH 7.4) to make the final concentration of the deferoxamine mesylate solution 80 μg / mL.

[0052] (4) Weigh 375 mg of oxidized sulfated sodium alginate and dissolve it in 5 mL of the above-mentioned deferoxamine mesylate solution to a final concentration of 75 mg / mL; dissolve 120 mg of adipic acid dihydrazide (ADH) in 8 mL of the above-prepared deferoxamine mesylate solution to a final concentration of 15 mg / mL; place the two solutions in a centrifuge tube at room temperature in a volume ratio of 8:2, mix and vortex for 10 minutes, and obtain sulfated sodium alginate hydrogel (S-OSA-DFO).

[0053] Example 2: Various properties of sulfated sodium alginate hydrogel

[0054] 1. Structural characterization of sulfated sodium alginate hydrogel

[0055] The microscopic morphology of the S-OSA-DFO hydrogel prepared in Example 1 was characterized by scanning electron microscopy. The S-OSA-DFO hydrogel was molded into a cylinder with a diameter of 14 mm and a height of 7 mm (Φ14 mm×7 mm), and the hydrogel was frozen overnight at -80°C and freeze-dried for 2 days at -50°C and 20 mbr to obtain a dry hydrogel cylinder. The dried sample was cut and fixed on a sample plate with conductive tape. After vacuum gold spraying, the surface morphology of the sample was observed under a JSM-6390LV low vacuum scanning electron microscope.

[0056] SEM photos are shown in Figure 1 The interior of the hydrogel presents a dense network of pores with a regular structure. The porous structure of the hydrogel simulates the structure of the extracellular matrix, which can promote cell adhesion, sustained release of drugs, and exchange and transport of oxygen and metabolites.

[0057] 2. Self-healing and injectability of sulfated sodium alginate hydrogel

[0058] The S-OSA-DFO hydrogel cylinder was stained with methylene blue and methyl orange, respectively. After being cut in the middle with a blade, the blue half cylinder and the orange half cylinder were assembled. After 10 minutes, the assembled hydrogel was picked up with tweezers to observe whether the assembled hydrogel was separated under gravity.

[0059] When the S-OSA-DFO hydrogel is in a solution state, it is sucked into a disposable syringe. After the S-OSA-DFO is gelled, the core rod of the syringe is pushed to observe whether the hydrogel can be pushed out of the syringe under the action of shear force.

[0060] Self-healing results Figure 2AAs shown, the hydrogel was first dyed, then cut into two halves, and the halves of the hydrogels of different colors were attached together. After 3 hours, the hydrogel healed automatically, indicating that S-OSA-DFO can heal itself after being damaged without any external stimulation. The hydrogel was clamped with tweezers. Under the action of gravity, the attached hydrogel did not separate, and no obvious fracture marks were observed, confirming that the hydrogel of the present invention has good self-healing properties.

[0061] Injectability results such as Figure 2B As shown, before the hydrogel is "solidified", its solution is sucked into a disposable syringe. After standing for a period of time, the disposable syringe is inverted. When the hydrogel solution no longer flows, the core rod of the syringe is pushed, and the hydrogel can be squeezed out of the needle of the syringe without breaking, indicating that the hydrogel of the present invention is injectable.

[0062] 3. In vitro drug release from sulfated sodium alginate hydrogel

[0063] Preparation of DFO reference solution: Accurately weigh 65.7 mg of deferoxamine mesylate (DFO) and dissolve it in a 100 mL volumetric flask, add ultrapure water to make up to volume to obtain a 1.0 mmol / mL DFO reference solution.

[0064] Preparation of FeCl3 reference solution: Accurately weigh 48.67 mg of ferric chloride hexahydrate and dissolve it in a 100 mL volumetric flask, add ultrapure water to make up to volume to obtain a 3.0 mmol / mL FeCl3 reference solution.

[0065] The release of DFO from S-OSA-DFO hydrogel was carried out by half-liquid replacement method in PBS solutions with different pH values ​​(pH=7.4 or pH=4.8). The hydrogel was molded into a Φ14mm×7mm cylinder, placed in a 50mL centrifuge tube, and 30mL of PBS buffer solution with a pH value of 7.4 or 4.8 was added, and shaken at 37°C (100rpm). At certain time points (0.5, 1, 4, 12, 24, 48, 96h), 15mL of solution was collected from the centrifuge tube and supplemented with 15mL of new PBS solution.

[0066] Preparation of DFO standard curve: Accurately weigh a certain amount of deferoxamine mesylate powder, use double distilled water to prepare standard solutions of 20, 40, 80, 160, 320, and 640 μg / mL, take 2 mL of each standard solution, and then add an equal volume of FeCl3 reference solution, and detect its absorbance at a wavelength of 430 nm. With the concentration of DFO standard solution as the horizontal axis and the absorbance as the vertical axis, draw the standard curve and calculate the regression equation of the working curve.

[0067] Sample solution determination: Add 15 mL of FeCl3 reference solution to the collected solution, detect its absorbance at 430 nm, and calculate the concentration of DFO based on the standard curve.

[0068] The results are as follows Figure 3 As shown in the figure, S-OSA-DFO hydrogel achieved sustained release of DFO and did not show sudden release in the initial stage. In addition, the release rate of the hydrogel at pH 4.8 was faster than that at pH 7.4.

[0069] 4. Analysis of the physical and chemical properties of sulfated sodium alginate hydrogel

[0070] The cyclic compression and rheological properties of the S-OSA-DFO hydrogel prepared in Example 1 were tested to evaluate its physicochemical properties.

[0071] 1. Loop Compression

[0072] The sulfated sodium alginate hydrogel S-OSA-DFO was made into a straight cylindrical sample using a mold, and its cyclic compression and single extrusion were measured using a texture analyzer to detect the anti-fatigue behavior and compressive strength of the hydrogel. The physical experiment used a 100N maximum force sensing element and probe for compression, with a compression deformation of 40%, a trigger force of 0.15N, an initial height of 20mm, and a probe descending speed of 10mm / min.

[0073] 2. Rheological properties

[0074] The sulfated sodium alginate hydrogel S-OSA-DFO was molded into a cylindrical sample and rheologically tested by a rheometer using a parallel plate with a diameter of 50 mm. A frequency sweep of 1-20 Hz was performed at 37°C and a deformation of 10% to explore the relationship between the storage modulus (G') and loss modulus (G") of the hydrogel and the shear frequency f.

[0075] The results are as follows Figure 4 As shown, the sulfated sodium alginate hydrogel has good cycling performance and rheological properties. Specifically, at all frequencies (1-20Hz), the hydrogel maintains the state of G'>G", indicating that there are stable covalent bonds inside the hydrogel. The G' value of the hydrogel is between 3.0±1.1kPa, and the storage modulus of the S-OSA-DFO hydrogel is about 3.0kPa, indicating that the hydrogel is suitable for application to human skin, laying the foundation for subsequent animal experiments.

[0076] Example 3: Hemolytic activity of sulfated sodium alginate hydrogel

[0077] Blood compatibility is considered one of the most important reference standards for evaluating whether biomaterials can be used for wound healing. Hemolysis rate is usually used as a reference indicator, which refers to the degree to which red blood cells are damaged by external factors and release hemoglobin into the plasma. The blood compatibility of sulfated sodium alginate hydrogel was tested by adding red blood cell suspension to it.

[0078] Test sample: the sulfated sodium alginate hydrogel sample S-OSA-DFO prepared in Example 1, the positive control was 1% Triton X-100, and the negative control was PBS buffer solution.

[0079] Experimental method: Blood was collected from normal rats through the abdominal aorta, the supernatant was discarded by centrifugation, the red blood cells were resuspended with saline until the supernatant was clear, the red blood cells were diluted to 5% with saline, 100 mg of hydrogel was soaked in a mixed solution of 500 μL 5% red blood cell suspension and 500 μL PBS buffer solution, incubated at 37°C and 100 rpm for 1 hour, the supernatant was centrifuged and its absorbance was measured at a wavelength of 540 nm. The hemolysis rate was calculated as follows:

[0080] Hemolysis rate (%) = (Ah-Ap) / (At-Ap)×100%.

[0081] Among them, A h Represents the absorbance of red blood cells treated with different hydrogels, A p represents the absorbance of PBS-treated red blood cells, A t Represents the absorbance of erythrocytes treated with 1% Triton X-10.

[0082] The results are as follows Figure 5 As shown, compared with the control group, the hemolysis rate of sulfated sodium alginate hydrogel was extremely low, which met the national requirements.

[0083] Example 4: Cell viability and migration experiments of sulfated sodium alginate hydrogels

[0084] Cell experiments were performed to evaluate the effects of sulfated sodium alginate hydrogel on cell viability and cell migration ability.

[0085] Test sample: the sulfated sodium alginate hydrogel sample S-OSA-DFO prepared in Example 1.

[0086] Cell viability assay: Normally grown NIH-3T3 fibroblasts were digested and plated in a 96-well plate, with 4 × 10 cells per well. 3The cells were cultured overnight at 37°C until they attached to the wall. The control group used complete DMEM medium; the experimental group used complete medium soaked in sulfated sodium alginate hydrogels, specifically, the complete DMEM high-glucose medium in the 96-well plate inoculated with NIH-3T3 cells was aspirated, and 100 μL of hydrogel extracts with concentrations of 10 mg / mL, 2 mg / mL, 0.4 mg / mL, 0.08 mg / mL, and 0.016 mg / mL were added (according to the hydrogel mass mg and the DMEM medium volume mL, the ratios were 10:1, 2:1, 0.4:1, 0.08:1, and 0.016:1, respectively). The 96-well plate was placed in an incubator at 37°C and 5% (v / v) CO2 for 24 hours, and then the hydrogel extract in the 96-well plate was discarded, and 110 μL of CCK-8 reagent diluted with complete DMEM high-glucose medium was added again, with each well containing 10 μL of CCK-8. The plate was placed in a cell culture incubator and cultured for 40-60 minutes. The cell viability was determined using an enzyme marker at a wavelength of 450 nm.

[0087] Cell migration experiment: Normally grown NIH-3T3 mouse fibroblasts were digested and inoculated in 6-well plates at 2×106 cells per well. The cells were cultured at 37°C until the 6-well plates were fully confluent. The complete DMEM high-glucose medium in the 6-well plates inoculated with NIH-3T3 cells was aspirated, scratched with a 10 μL pipette tip, and the cell fragments were washed 3 times with PBS. The control group used complete medium DMEM, and the experimental group used complete medium soaked in sulfated sodium alginate hydrogel. At predetermined time points (0, 6, 12 and 24 h), the distance of cell migration was measured and images were taken.

[0088] The results are as follows Figure 6-7 As shown in the figure, compared with the control group, the survival rate of the S-OSA-DFO hydrogel group was ≥90%, with no obvious cytotoxicity and good cell compatibility. The cells treated with S-OSA-DFO hydrogel had obvious migration after scratching, and the migration effect was obvious, indicating that sulfated sodium alginate hydrogel has a certain promoting effect on the proliferation and migration of cells in the wound.

[0089] Example 5: Experiment on the effect of sulfated sodium alginate hydrogel on wound healing in diabetic rats

[0090] The sulfated sodium alginate hydrogel S-OSA-DFO in Example 1, the control group was a sodium alginate sponge dressing, and the blank was normal saline.

[0091] Experimental methods:

[0092] The rat diabetes model was established by intraperitoneal injection of high-dose streptozotocin (STZ) to establish a rat model of type Ⅰ diabetes.

[0093] 80 5-6 week old SD rats were adaptively fed for one week until their body weight reached about 200 g. After fasting but not depriving of water for 12 hours, a single large dose of streptozotocin (70 mg / kg, STZ dissolved in 0.1 M sodium citrate buffer with pH = 4.2 in an ice bath) was injected intraperitoneally within 30 minutes to induce diabetes in the rats.

[0094] Three days and one week after the injection, the fasting blood glucose levels of the rats were tested by blood sampling from the tail vein using a blood glucose meter, and rats with blood glucose levels ≥16.7mmol / L were selected for subsequent experiments. Excluding the rats that died or failed to be modeled, 65 rats were successfully modeled.

[0095] 65 diabetic rats with successful modeling were intraperitoneally injected with 1 mL of 10% chloral hydrate. When there was no obvious reaction when the toes of the rats were pinched with tweezers, the backs of the diabetic rats were depilated with a shaver and depilatory cream, and wounds were made with a skin needle biopsy punch with a diameter of 0.6 cm. Full-thickness wounds were constructed on the back. Except for the rats that died due to anesthesia and modeling, 54 rats were successfully modeled.

[0096] The rats with successful modeling were randomly divided into 3 groups: blank group, control group, and S-OSA-DFO hydrogel group. The hydrogel was filled into the wound site and covered with 3M film.

[0097] 1. Wound healing on the back of rats

[0098] The dressing of diabetic rats with full-thickness wounds was changed every 2 days, and the wound area was photographed with a camera on days 0, 5, 10, and 14 to calculate the degree of wound closure.

[0099] The results are as follows Figure 8 As shown, on the 5th day, the wound healing rate of S-OSA-DFO was faster than that of other groups. On the 10th day, the wound healing of the S-OSA-DFO hydrogel group showed significant improvement, indicating that S-OSA-DFO hydrogel has a good wound healing effect.

[0100] 2. Rat skin wound recovery experiment

[0101] The wound sites of rats with full-thickness diabetic wounds were sampled on days 5, 10, and 14, respectively. The samples were preserved in paraformaldehyde and placed in xylene, anhydrous ethanol, hematoxylin, hydrochloric acid alcohol and other dyes for H&E and Masson staining.

[0102] As shown in Figure 9, the sulfated sodium alginate hydrogel S-OSA-DFO has obvious re-epithelialization and collagen deposition. Fig.9A), on day 5, the S-OSA-DFO hydrogel group had already shown re-epithelialization, while no obvious re-epithelialization was observed in the other hydrogel groups. On day 10, the S-OSA-DFO hydrogel group had already shown some hair follicles, while the other groups showed only partial re-epithelialization. On day 14, HE staining of wound skin tissue showed that the S-OSA-DFO hydrogel group was almost completely re-epithelialized, with an epidermal thickness of 123.93±1.9μm, and the wound showed a basic epithelial structure with a large number of hair and hair follicles, similar to normal skin tissue. There was no significant difference between the control group and the blank group on days 5, 10, and 14.

[0103] Masson staining showed ( Fig. 9B ), from the analysis of the degree of collagen staining and density, the amount of collagen deposition in the S-OSA-DFO hydrogel group increased significantly over time, while the control group and the blank group only increased slightly and moderately. On the 5th day, there was no significant difference in the amount of collagen deposition in each group; on the 10th day, there was no significant difference between the blank group and the positive control group, while the amount of collagen deposition in the S-OSA-DFO hydrogel group increased visibly. The analysis showed that DFO promoted the formation of new blood vessels and accelerated the remodeling of granulation tissue. On the 14th day, the collagen deposition in the S-OSA-DFO hydrogel group was 75.4%, while the blank and positive controls were 52.5% and 44.9%, respectively. Therefore, S-OSA-DFO hydrogel can accelerate the formation of granulation tissue, re-epithelialization and collagen deposition, enhance the therapeutic effect of diabetic wounds, and accelerate the closure speed of diabetic wounds.

[0104] 3. Determination of inflammation and related factors

[0105] The skin of the back of the rat was removed and preserved in paraformaldehyde. The sections were dewaxed in xylene for 15 minutes, repeated three times, dehydrated with anhydrous ethanol for 5 minutes, washed with 85% and 75% ethanol gradients twice, washed with distilled water, and antigen repaired in citric acid anti-inflammatory repair buffer (8 minutes of medium heat until boiling, stop the fire for 8 minutes and keep warm and turn to low heat for 7 minutes, cool naturally and place in PBS for shaking and washing for 5 minutes, repeated three times), incubated in 3% hydrogen peroxide in the dark for 25 minutes, washed with PBS for 5 minutes, repeated three times, 3% BSA was added to the tissue circle to evenly cover the tissue, Block at room temperature for 30 minutes, shake off the blocking solution, add primary antibody prepared in PBS, block overnight in a humidified box at 4°C, wash and decolorize with PBS for 5 minutes, repeat three times, cover with secondary antibody and incubate at room temperature for 50 minutes, wash and decolorize with PBS for 5 minutes, repeat three times, spin dry the slices and add DAB color developing solution in the circle, rinse with tap water to stop color development, counterstain with hematoxylin for 3 minutes, wash with tap water, differentiate with hematoxylin differentiation solution, wash with tap water, blue with hematoxylin blueing solution, rinse with running water, dehydrate with 75%, 85%, and 100% ethanol for 5 minutes, make transparent with xylene for 5 minutes, and seal with neutral resin.

[0106] The results are as follows Fig.10 As shown in the figure, IL-6 and TNF-α are inflammatory factors produced by many types of cells and play an important role in inflammatory responses. There was no significant difference in the number of inflammatory factors between the blank group and the positive control group; the expression of inflammatory factors in the wound site of the S-OSA-DFO hydrogel group was generally lower than that of the other groups on the 5th day, and it decreased significantly with the extension of time. And on the 10th and 14th days, there was more expression of VEGF and CD31 in the wound site of the S-OSA-DFO hydrogel group. This shows that S-OSA-DFO hydrogel can relieve chronic inflammation in the early stage of wound repair, promote angiogenesis in the later stage of wound repair, and enhance the healing effect of diabetic wounds.

[0107] The above results indicate that the S-OSA-DFO hydrogel group has a significant effect in promoting wound healing. The hydrogel that combines the ability to adsorb inflammatory factors and promote angiogenesis has great potential for the repair of chronic inflammatory wounds caused by diabetes.

[0108] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.

Claims

1. A method for preparing sulfated sodium alginate hydrogel, characterized in that: The preparation method specifically comprises the following steps: (1) dissolving sodium alginate in a chlorosulfonic acid formamide mixed solution to react, obtaining sulfated sodium alginate, re-dissolving by alcohol precipitation, dialysis and freeze-drying to obtain sulfated sodium alginate; (2) dissolving sulfated sodium alginate and sodium periodate in ultrapure water, quenching with ethylene glycol after the reaction in the dark, and freeze-drying to obtain oxidized sulfated sodium alginate; (3) dissolving deferoxamine mesylate in a buffer solution containing polyethylene glycol to obtain a deferoxamine mesylate solution; (4) dissolving oxidized sulfated sodium alginate in a deferoxamine mesylate solution to obtain solution A; dissolving adipic acid dihydrazide in a deferoxamine mesylate solution to obtain solution B; (5) Mix solution A and solution B evenly to obtain sulfated sodium alginate hydrogel.

2. The method for preparing the sulfated sodium alginate hydrogel according to claim 1, characterized in that: In the step (1), the mass volume ratio of the sodium alginate and chlorosulfonic acid formamide mixed solution is 1:8-10, wherein the chlorosulfonic acid formamide mixed solution is prepared by mixing chlorosulfonic acid and anhydrous formamide in a volume ratio of 1:4-6.

3. The method for preparing the sulfated sodium alginate hydrogel according to claim 1, characterized in that The final concentration of the deferoxamine mesylate solution in step (3) is 60 μg / mL-100 μg / mL.

4. The method for preparing the sulfated sodium alginate hydrogel according to claim 1, characterized in that: In step (4), the final concentration of solution A is 50 mg / mL-100 mg / mL, and the final concentration of solution B is 5 mg / mL-20 mg / mL.

5. The method for preparing the sulfated sodium alginate hydrogel according to claim 1, characterized in that: In the step (5), solution A and solution B are mixed in a volume ratio of 3 to 5:1 and vortexed at room temperature for 10 min to 30 min.

6. The sulfated sodium alginate hydrogel prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The sulfated sodium alginate hydrogel is formed by cross-linking oxidized sulfated sodium alginate, adipic acid dihydrazide, polyethylene glycol and deferoxamine mesylate.

7. Use of the sulfated sodium alginate hydrogel according to claim 6 in the preparation of an external medicine for repairing chronic wounds.

8. The use according to claim 7, characterized in that: The chronic wound is caused by trauma and diabetic complications.

9. The use according to claim 7, characterized in that: Filling the sulfated sodium alginate hydrogel into the wound site of chronic trauma can promote the formation of new blood vessels and inhibit inflammation, thereby promoting wound healing.

Citation Information

Patent Citations

  • Preparation method of injectable natural polysaccharide self-healing hydrogel

    CN103910894A

  • Injectable self-healing hydrogel based on methyl vinyl ether-maleic acid copolymer / sodium alginate oxide and preparation method thereof

    CN105646893A